The Downstream Effects of Teacher Well-Being Programs: Improvements in Teachers' Stress, Cognition and Well-Being Benefit Their Students - Carroll, Annemaree; York, Ashley; Fynes-Clinton, Sam; Sanders-O'Connor, Emma; Flynn, Libby; Bower, Julie M.; Forrest, Kylee; Ziaei, Maryam (Frontiers in Psychology, 2021)
Quality interventions addressing the important issue of teacher stress and burnout have shown promising outcomes for participating teachers in terms of decreased distress, improved well-being and increased commitment to their jobs. Less is known however about whether such interventions also benefit students. The present study investigated the downstream effects for a completer sample of 226 primary and high school students after their teachers (n = 17) completed one of two 8-week stress reduction interventions. The relationships between change in teacher self-reported distress and burnout after completing the interventions, and change in students’ self-reported well-being, academic self-perceptions, and perceptions of classroom environment were explored. A secondary aim of this study was to assess whether changes in teachers’ cognitive flexibility mediated the relationship between teacher and student self-report outcomes. Results of correlational and multi-level mediation analyses showed that changes to teachers’ self-reported distress and burnout affected multiple facets of students’ well-being and the academic environment. Specifically, reductions in teachers’ self-reported distress and burnout were related to students’ improved perceptions of their teachers’ support in the classroom. Reductions in teachers’ personal- and work-related burnout correlated with greater increases of academic self-perception in students. Contrary to predictions, cognitive flexibility in teachers did not mediate the relationship between these student and teacher measures. These findings indicate important downstream benefits for students and highlight the broader value of stress-reduction and well-being programs for teachers.